(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Plyometric training is comparatively new pattern of training used for improving the vertical jumping performance. However, its effectiveness has been confirmed elsewhere. In this study effect of the Plyometric training has been evaluated in perspectives of Volley Ball players. Objectives: Evaluation of the effect of eight weeks plyometric training with regard to the vertical jumping performance, body fats and Heart Rate of the players were the main objectives of the study. Methodology: A pre and post-experimental design was used with an experimental group and control group of Volley Ball players. Experimental group got plyometric training and control group followed their routine of daily life. Pre and post-test data were taken and analyzed for observing the effect of plyometric training. Results: Difference between pretest and posttest scores on all the different variables was observed in experimental group, and no differences were observed in the control group. One-way analysis of variance and paired sample t- test indicated a significant improvement at the 0.05 level in Vertical Jumping, body fats and heart rate of the respondents. Conclusion: Findings of the present study have confirmed that plyometric training has very positive and encouraging effect on the vertical jumping performance and body fats percentage and heart rate of the respondents. Plyometric training may be used for the improvement of the jumping performance, body fats percentage and heart rate of the amateur and as well as professional players.